Protecting Children's Rights in Marriage Dispensation Cases: Evidence from Religious Courts in Indonesia - Dede Kania; Siti Nur Fatoni (Asy-Syari'ah, 2023)
The protection of children's rights is essential to ensure their well-being and development. In Indonesia, Law No. 16 of 2019 raised the minimum marriage age to 19 years, yet marriage dispensation remains an option for underage marriage in exceptional circumstances. This research examines trends in marriage dispensation cases in West Java and their implications for children's rights. The study employs an empirical, philosophical, sociological, and historical juridical approach, analyzing decisions from ten religious courts between 2019 and 2021. Findings reveal a significant increase in marriage dispensation cases after the law's enactment, driven by fears of moral transgressions (87%) and pre-marital pregnancies (8%). Despite legal provisions, 99% of applications were granted, often prioritizing cultural and religious norms over the principle of the child's best interests. This study highlights the need for strengthened judicial oversight and community engagement to align legal practices with protecting children's rights. The findings call for more robust preventive measures and an evaluation of the dispensation process to ensure compliance with the rights-based framework.